DORONGAN PEMERINTAH DALAM MENGEMBANGKAN PASAR MODAL (INVESTASI) PADA ERA MILENIAL DI INDONESIA - Helmi Helmi; Afrijal Afrijal; Nurul Izzah (Journal of Political Sphere, 2022)
AbstractThis research is to answer the problems faced by the Indonesian government in developing the capital market (investment) in the millennial era in Indonesia, the government has made various efforts to develop investment in Indonesia. However, the influence of digital technology is not immediately used by the Indonesian people, especially young people. The purpose of this study is to identify and explain government support to young people in order to increase investment for their future. This study uses a library research methodology, where the data obtained are obtained through valid documents The results of this study are that the government has made various efforts to encourage the development of investment for young people, the implications of this policy have an impact on the development of investment in Indonesia, the government's encouragement to get a good response among young people to invest, this success is due to maximum planning by the government through thorough socialization It is hoped that the government will continue to make efforts to develop investment by establishing programs that inspire and motivate people to continue investing.Keywords: Government, Investment and Indonesian Millennials